Inscrições em latim sob uma abordagem dialógica: um estudo no contexto do Cariri cearense - Leite, Francisco de Freitas (2014)
This research is based on the challenge of thinking a relevant and viable way to approach an alternative, discursive view of Latin. It is oriented by Bakhtin Circle‟s dialogical theory, considering its view of language from the perspective of social interaction and its ideological, historical and cultural components: this theory presents itself as a heuristic possibility to realize discursive studies on Latin. Although, as it would be impracticable to analyze every single genre of discourse present in Latin, this thesis investigates only the genres that are textualized as inscriptions in Latin (epigraphs, epitaphs, mottos and legends). As planned in this work‟s methodology, after the principles of the dialogical theory are reviewed and the theoretical axis of the research is defined, the thesis systematizes a theoretical-methodological propose of approaching inscriptions (written) in Latin from the perspective of genres of discourse. Then, following such proposal, it goes through an analytical study of a corpus composed by those inscriptions that are found nowadays (XXI century‟s first decades) at Cariri region of Ceará, Brazil the space and time context , emphasizing the interpretation of meaning of the concrete enunciates as they are inserted sociocultural and historical-ideologically. At last, the thesis presents the results of a study on the Cariri‟s context in which Latin is seen as a language with valid uses contemporarily, such as for textualize enunciates built from discourses of the official culture‟s ideology and loaded with objectives of reinvigorating points of view and values from the hegemonic elite. These results are in accordance to the thesis that a theoretical-methodological approach of Latin that considers enunciatively that language from the genres of discourse that make it, in certain time and space contexts, constitutes a heuristic alternative through which the Latin studies can advance, especially as it touches on the theme of the meaning construction.